1997
DOI: 10.3354/meps147129
|View full text |Cite
|
Sign up to set email alerts
|

Particle mixing by the polychaete Capitella species 1:coupling fate and effect of a particle-bound organic contaminant (fluoranthene) in a marine sediment

Abstract: Particle mixing by the polychaete Capitella sp. 1 was investigated in a 22 d microcosm experiment in the presence and absence of the sediment-bound polycycllc aromatic hydrocarbon (PAH) fluoranthene. Mixing by Capilella sp. 1 (30000 ind. m-') was examined using glass bead tracers (diam. = 30 to 100 pm) with and without a pulse introduction of fluoranthene to the sediment surface. Worms hdd a profound effect on the sediment appearance and reworked sediment in a conveyor-belt fashion. The predominant mode of mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 48 publications
2
33
0
1
Order By: Relevance
“…It has also been shown that PAH degradation in marine sediments is enhanced by stimulation of microbial activity in the presence of Capitella (Bauer et al 1988;Gardner et al 1979). On the other hand, Madsen et al (1997) found that the presence of Capitella increased the downward transport of the PAH, fluoranthene in surface sediment. However, a downward transport of AC is not likely due to the low sediment depth of maximum 1 cm in the present study.…”
Section: Ac Concentrationmentioning
confidence: 89%
See 1 more Smart Citation
“…It has also been shown that PAH degradation in marine sediments is enhanced by stimulation of microbial activity in the presence of Capitella (Bauer et al 1988;Gardner et al 1979). On the other hand, Madsen et al (1997) found that the presence of Capitella increased the downward transport of the PAH, fluoranthene in surface sediment. However, a downward transport of AC is not likely due to the low sediment depth of maximum 1 cm in the present study.…”
Section: Ac Concentrationmentioning
confidence: 89%
“…C. teleta is described as opportunistic and has a widespread distribution (Grassle 1980;Grassel and Grassel 1976) with population densities in the range of <100-400,000 worms m −2 (Méndez et al 1997;Tsutsumi 1987Tsutsumi , 1990. Several studies have examined the effects of chemical compounds on worm growth rate, sediment processing (Madsen et al 1997;Méndez et al 2001;Selck et al 1998Selck et al , 1999Selck et al , 2003, mortality (Méndez 2006) and life-history traits (Linke-Gamenick et al 1999, 2000aPedersen et al 2009;Ramskov et al 2009). The interactions between Capitella and microbial activities (Alongi 1985) and degradation of chemicals in sediment (Gardner et al 1979) have also been studied, where the presence of Capitella increased both of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Grassle & Grassle 1974, 1976, Pearson & Rosenberg 1978, Mén-dez et al 1997. C. capitata plays an important role in improving physicochemical properties of polluted sediments through its bioturbating activities (Gardner et al 1979, Chareonpanich et al 1993, Madsen et al 1997. C. capitata represents a cryptic species complex, in which adult morphology is so similar among species that no effort has been made to separate this complex with proper taxonomical species-descriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Davis 1974, Rhoadsaffects fluxes of organic matter, nutrients and contaminants across the sediment-water interface and within the sediment column (e.g. Aller 1982, Kristensen & Blackburn 1987, Gérino 1990, Kure & Forbes 1997, Madsen et al 1997. The characterization and quantification of bioturbational processes in sediments allow us to determine the fate of the matter that settles at the sediment surface, and are therefore of primary concern in biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%